2008
DOI: 10.1016/j.whi.2008.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Improving Women's Preconceptional Health

Abstract: Purpose-Improving the health of women before pregnancy is an important strategy for reducing adverse pregnancy outcomes for mother and child. This paper reports the first pretest-posttest results from a randomized trial of a unique, multidimensional, small group format intervention, Strong Healthy Women, designed to improve the health behaviors and health status of preconceptional and interconceptional women.Methods-Nonpregnant pre-and interconceptional women ages 18−35 were recruited in 15 lowincome rural com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 22 publications
3
39
0
Order By: Relevance
“…In total, 12 studies met the inclusion criteria for our search. [24][25][26][27][28][29][30][31][32][33][34][35] (See the Supplementary file, in the ARTICLE TOOLS section on the journal site.) No additional studies were identified through hand searches of these studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 12 studies met the inclusion criteria for our search. [24][25][26][27][28][29][30][31][32][33][34][35] (See the Supplementary file, in the ARTICLE TOOLS section on the journal site.) No additional studies were identified through hand searches of these studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A majority of studies also received a weak rating on blinding (n = 7, 58%); 24,[27][28][29][33][34][35] this was mostly due to study design (e.g., pre-post) and the nature of the interventions, resulting in awareness among both assessors and participants of intervention status. A similar number of studies received a weak rating on data collection methods (n = 7, 58%) 24,26,[28][29][30]34,35 because most authors did not use validated tools or did not report their psychometric properties. Finally, five (42%) of the studies received a weak rating for withdrawals and dropouts because of high attrition (52%-77%) or unreported follow-up rates.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations